MIKROBA DALAM PERSPEKTIF LINGKUNGAN HIDUP - Rofieq, Ainur (Jurnal Bestari, 1991)
For periods, microbs was conceived as the great enemy of mankind. Since, its dangerous behaviour to human health. The role of microba is now the vice versa when the scientists found the positive aspects of its behaviour. One of its positive roles is the effective solution to destroy ecoterorism. To make the behaviour of microba usefull for human environment, is only up to mankind